Costimulation Blockade in Vascularized Composite Allotransplantation - Giannis, Dimitrios; Moris, Dimitrios; Cendales, Linda C. (Frontiers in Immunology, 2020)
Vascular composite allotransplantation (VCA) is a field under research and has emerged as an alternative option for the repair of severe disfiguring defects that result from infections or traumatic amputation in a selected group of patients. VCA is performed in centers with appropriate expertise, experience and adequate resources to effectively manage the complexity and complications of this treatment. Lifelong immunosuppressive therapy, immunosuppression associated complications, and the effects of the host immune response in the graft are major concerns in VCA. VCA is considered a quality of life transplant and the risk-benefit ratio is dissimilar to life saving transplants. Belatacept seems a promising drug that prolongs patient and graft survival in kidney transplantation and it could also be an alternative approach to VCA immunosuppression. In this review, we are summarizing current literature about the role of costimulation blockade, with a focus on belatacept, in VCA.